2003
DOI: 10.4314/wsa.v29i2.4847
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a textile dye in the anaerobic baffled reactor

Abstract: Synthetic organic colourants, the majority of which are recalcitrant in nature, are used in many different manufacturing processes. The dyes are released into the environment in industrial effluents and are highly visible even at low concentrations (< 1 mg/l). Decolorisation of the dye CI Reactive Red 141 was investigated in a laboratory-scale anaerobic baffled reactor (ABR). The results of the physical decolorisation tests suggested significant decolorisation due to adsorption to the biomass; however, it is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 4 publications
1
32
0
1
Order By: Relevance
“…In case of undiluted effluent, Typha sp.-based CWs removed maximum amount of COD followed by Azolla sp.-based CWs. Treatment of textile dye using anaerobic baffled reactor by wetland plants removed 70-90% COD (Bell and Buckley 2003;Haris 2007). Tegegne et al (2008) noticed significant difference (56.0-91.5%) in the concentration of COD when the effluents from various industries were treated with wetlands.…”
Section: Discussionmentioning
confidence: 99%
“…In case of undiluted effluent, Typha sp.-based CWs removed maximum amount of COD followed by Azolla sp.-based CWs. Treatment of textile dye using anaerobic baffled reactor by wetland plants removed 70-90% COD (Bell and Buckley 2003;Haris 2007). Tegegne et al (2008) noticed significant difference (56.0-91.5%) in the concentration of COD when the effluents from various industries were treated with wetlands.…”
Section: Discussionmentioning
confidence: 99%
“…La pollution due aux effluents des industries textiles peut être réduite en adoptant des méthodes de traitement adéquates (traitements physico-chimique, biologique, électrochimique ou par oxydation avancée). Dans certains laboratoires des universités africaines, des travaux sont en cours pour la mise au point des méthodes de traitement physico-chimique ou biologique [25][26][27][28]. Comme on peut le voir, le manque de législation ou la non application des réglementations en vigueur en matière de gestion des eaux usées industrielles au Togo expose les milieux aquatiques et terrestres à toute forme de pollution dont les conséquences, à court ou à long terme, finiront par atteindre l'homme.…”
Section: Discussionunclassified
“…ABR was effective to reduce color concentration up to 65%. Bell & Buckley [11] reported that the use of ABR to treat textile wastewater could reduce color concentration up to 86%. The decrease of color concentration was more effectively performed on ABR than RBC.…”
Section: Resultsmentioning
confidence: 99%